تطوير خوارزمية كاش الويب GDFS باستخدام مسافة غوغل المقيّسة - سليمان, علي; الديباجة, ايهاب (Latakia University Journal -Engineering Sciences Series, 2018)
This paper presents a proposed development of the GDFS algorithm for the Web Cache technology by introducing the Normalized Google Distance (NGD) distance to the algorithm's replacement function to determine the semantic similarity between the objects in the cache and thus support the original algorithm replacement decision when specifying the objects which must be evicted from the cache The study was applied on the information systems operating in Lattakia Port, The results showed that the introduction of semantic similarity using NGD raised the Hit Rate compared to the original algorithm as it improved system performance by reducing page loading time compared with the original successor replacement of the algorithm. تقدّم هذه الورقة البحثية تطويراً مقترحاً لخوارزمية (Greedy Dual Frequency Size) GDFS الخاصة بتقنية كاش الويب من خلال إدخال مسافة غوغل المقيّسة NGD(Normalized Google Distance) إلى تابع الاستبدال Replacement Function الخاص بالخوارزمية لتحديد التشابه الدلالي Semantic Similarity بين الأغراض الموجودة في الكاش، وبالتالي، دعم قرار تابع الاستبدال الأصلي الخاص بالخوارزمية لدى تحديد الأغراض الواجب إخراجها evicted من الكاش. تمّ تطبيق الدراسة على أنظمة المعلومات العاملة في الشركة العامة لمرفأ اللاذقية، بينت النتائج أنّ إدخال التشابه الدلالي باستخدام مسافة غوغل المقيسة رفع من معدل الإصابة Hit Rate مقارنةً مع الخوارزمية الأصلية، كما تحسن أداء النظام من خلال تخفيض زمن تحميل الصفحة مقارنةً مع تابع الاستبدال الأصلي للخوارزمية.